Strategi Pengembangan Destinasi Wisata Pada Pasca Pandemi Covid-19 di Taman Mini Indonesia Indah (TMII) - Febrian Gabe Tampubolon; Jamalia Sowakil; Kameda Delen; Tomas Jorgi (Peneliti.net, 2023)
The existence of the Covid-19 pandemic has had a big impact on various sectors of people's lives. The government issued various policies to reduce the spread of Covid-19, one of which was the policy of closing tourist attractions which resulted in a decrease in tourist visits, economic growth and local revenue. During the post-Covid 19 pandemic, tourism began to open and increase again, one of which was the Taman Mini Indonesia Indah (TMII) tourist destination. After transferring ownership and then being renovated by the Central Government, TMII with this new nuance has been re-opened and promoted. This study aims to identify and analyze the development of TMII tourist destinations, supporting factors and tourism development strategies in the post-Covid-19 pandemic at TMII.Descriptive qualitative research method with data collection techniques of research literature, observation, and documentation. Then analyzed using data triangulation and Analytical Hierarchy Process (AHP). The results of the discussion obtained by the authors in this study are tourism development strategies in the post-Covid-19 pandemic, namely promotion on social media, carrying out branding, and increasing tourist attractiveness. TMII Tourism Development in the post-Covid-19 Pandemic period in East Jakarta has been quite optimal, as can be seen from the facilities and infrastructure that are well managed and road access to tourist attractions that are already available and the accessibility is quite smooth. Supporting factors in the development of TMII tourist destinations, namely: Varied rides and the charm of beautiful land arrangement, varied choices of recreational tourism activities, facilities for selling souvenirs and food and drink, easy and available internet access and communication networks, and the spirit of the Pokdarwis of the community around the TMII location